Berani Pulih: Regulasi Emosi Korban Toxic Relationship Dalam Membangun Resiliensi - Afandi, Nur; Ikhrom, Ikhrom; Nurfitri, Aldila Dyas (Jurnal Consulenza : Jurnal Bimbingan Konseling dan Psikologi, 2026)
Toxic relationships in dating are increasingly prevalent among adolescents and young adults and may lead to significant psychological consequences for the victims. This study aims to explore how victims of toxic relationships regulate their emotions in the process of developing resilience after experiencing dating violence. This research employed a qualitative approach with a case study design. Data were collected through semi-structured interviews with three female participants aged 17–22 years who had experienced unhealthy dating relationships. The data were analyzed using thematic analysis to identify patterns of emotional experiences and emotion regulation strategies used by the participants. The findings reveal that the participants experienced various forms of violence, including physical abuse, sexual coercion, economic exploitation, and possessive behaviors that restricted their personal freedom. These experiences triggered emotional responses such as sadness, anger, fear, and feelings of helplessness. Despite these challenges, the participants gradually developed coping strategies through emotion regulation, such as seeking social support, engaging in positive activities, and reconstructing healthier perspectives on relationships. The study highlights that adaptive emotion regulation and social support play crucial roles in helping victims of toxic relationships build resilience and move forward with their lives in a more constructive way. Keywords: Dating violence; Emotion regulation; Psychological recovery; Resilience; Toxic relationship.